The evaluation of a mobile user interface for people on the autism spectrum: An eye movement study. Issue 142 (October 2020) - Rezae, Mortaza; Chen, Nigel; McMeekin, David; Tan, Tele; Krishna, Aneesh; Lee, Hoe
Highlights: We use eye movement analyses to evaluate how individuals on the autism spectrum and non-autistic individuals interact with user interfaces. We find that users on the spectrum process user interfaces differently than neurotypicals. We found that autistic users process icons and images faster than texts. We also discovered that non-complementary icons and texts confuse autistic users. We anticipate our findings to inform user interface design for individuals on the autism spectrum. Abstract: Software solutions are increasingly used to facilitate independence for people on the autism spectrum. However, design guidelines to make software user interfaces easy to use have not been clearly defined. Here we show, through eye movement analyses, that autistic users interact differently with user interfaces than non-autistic users and make recommendations to improve user interface design. We found that autistic users process icons and images faster than texts. Using both icons and texts was also effective in facilitating comprehension. However, we discovered that non-complementary icons and texts confuse users. Our results illustrate that users on the autism spectrum process user interfaces differently than non-autistic users. We anticipate our findings to improve user interface design for individuals on the autism spectrum.